Summary of Kansas State University swine enterprise record 1995 - B T Richert; Michael R Langemeier; Robert D Goodband; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1995)
The Kansas Swine Enterprise Record Program evaluates biological and economic performance and is part of a cooperative record-keeping project with extension personnel and swine producers in Kansas, Nebraska, and South Dakota. From July 1, 1994 to June 31, 1995, profit per cwt of pork produced for these producers (37 semi-annual and 20 annual data) averaged 4.75 for the first 6 months of 1995, but a loss of 1.22 occurred for the past year. Producers in the top one-third in terms of profitability had average profits of 3.44 per cwt, whereas producers in the bottom one-third had average losses of 7.07 per cwt for the year. Critical factors separating low- and high-profit producers included feed costs, unpaid labor, fixed costs, and death loss.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Enterprise; Records; Analysis; Profitability